Joint hypermobility syndrome in rheumatology - A. M. Satybaldyev (Современная ревматология, 2017)
Joint hypermobility syndrome (JHS) is a disease characterized by symptoms of locomotor system involvement in the absence of obvious systemic rheumatic diseases (RDs). JHS accompanied by the symptomatology of RDs should be distinguished from isolated joint hypermobility, in which there are no complaints even in cases of its generalized manifestations and the patients feel virtually healthy. The paper provides an overview of the literature on the JHS. It gives diagnostic criteria for JHS (the Brighton criteria encompasses the Beighton score) and the clinical manifestation of damages to the locomotor apparatus, visceral organs, and skin in this syndrome. Autonomic nervous system dysfunction as a possible manifestation of JHS and its impact on the daily life of patients are discussed. Attention is paid to the prevention and treatment of JHS.